Repertoire of Naturally Acquired Maternal Antibodies Transferred to Infants for Protection Against Shigellosis - Ndungo, Esther; Andronescu, Liana R.; Buchwald, Andrea G.; Lemme-Dumit, Jose M.; Mawindo, Patricia; Kapoor, Neeraj; Fairman, Jeff; Laufer, Miriam K.; Pasetti, Marcela F. (Frontiers in Immunology, 2021)
Shigella is the second leading cause of diarrheal diseases, accounting for >200,000 infections and >50,000 deaths in children under 5 years of age annually worldwide. The incidence of Shigella-induced diarrhea is relatively low during the first year of life and increases substantially, reaching its peak between 11 to 24 months of age. This epidemiological trend hints at an early protective immunity of maternal origin and an increase in disease incidence when maternally acquired immunity wanes. The magnitude, type, antigenic diversity, and antimicrobial activity of maternal antibodies transferred via placenta that can prevent shigellosis during early infancy are not known. To address this knowledge gap, Shigella-specific antibodies directed against the lipopolysaccharide (LPS) and virulence factors (IpaB, IpaC, IpaD, IpaH, and VirG), and antibody-mediated serum bactericidal (SBA) and opsonophagocytic killing antibody (OPKA) activity were measured in maternal and cord blood sera from a longitudinal cohort of mother-infant pairs living in rural Malawi. Protein-specific (very high levels) and Shigella LPS IgG were detected in maternal and cord blood sera; efficiency of placental transfer was 100% and 60%, respectively, and had preferential IgG subclass distribution (protein-specific IgG1 > LPS-specific IgG2). In contrast, SBA and OPKA activity in cord blood was substantially lower as compared to maternal serum and varied among Shigella serotypes. LPS was identified as the primary target of SBA and OPKA activity. Maternal sera had remarkably elevated Shigella flexneri 2a LPS IgM, indicative of recent exposure. Our study revealed a broad repertoire of maternally acquired antibodies in infants living in a Shigella-endemic region and highlights the abundance of protein-specific antibodies and their likely contribution to disease prevention during the first months of life. These results contribute new knowledge on maternal infant immunity and target antigens that can inform the development of vaccines or therapeutics that can extend protection after maternally transferred immunity wanes.